Genome sequencing of the multicellular alga Astrephomene provides insights into convergent evolution of germ-soma differentiation - Shota Yamashita (Nature Portfolio, 2021)
Abstract Germ-soma differentiation evolved independently in many eukaryotic lineages and contributed to complex multicellular organizations. However, the molecular genetic bases of such convergent evolution remain unresolved. Two multicellular volvocine green algae, Volvox and Astrephomene, exhibit convergent evolution of germ-soma differentiation. The complete genome sequence is now available for Volvox, while genome information is scarce for Astrephomene. Here, we generated the de novo whole genome sequence of Astrephomene gubernaculifera and conducted RNA-seq analysis of isolated somatic and reproductive cells. In Volvox, tandem duplication and neofunctionalization of the ancestral transcription factor gene (RLS1/rlsD) might have led to the evolution of regA, the master regulator for Volvox germ-soma differentiation. However, our genome data demonstrated that Astrephomene has not undergone tandem duplication of the RLS1/rlsD homolog or acquisition of a regA-like gene. Our RNA-seq analysis revealed the downregulation of photosynthetic and anabolic gene expression in Astrephomene somatic cells, as in Volvox. Among genes with high expression in somatic cells of Astrephomene, we identified three genes encoding putative transcription factors, which may regulate somatic cell differentiation. Thus, the convergent evolution of germ-soma differentiation in the volvocine algae may have occurred by the acquisition of different regulatory circuits that generate a similar division of labor.